Risk zonation of submarine geological hazards in the Chengdao area of the Yellow River subaqueous delta - Wang, Zhenhao; Du, Xing; Sun, Yongfu; Song, Yupeng; Dong, Lifeng; Zhou, Qikun; Jiang, Weida (Frontiers in Marine Science, 2023)
Submarine geological disasters occur frequently in the Chengdao area of the Yellow River subaqueous delta, which seriously threaten the safe operation of marine engineering in the region. Therefore, it is of great significance to carry out risk zonation for this region. The current study presents a detailed assessment of risk zones related to submarine geological hazards in this region based on analytical hierarchy process (AHP). The system of assessment index for risk zonation was established with four aspects of hydrodynamic condition, engineering geological environment, disaster geological conditions and human engineering activities. Eight geological hazard evaluation factors were selected and the distribution characteristics of each evaluation factor were discussed in detail by combining qualitative analysis and quantitative calculation. The risk level of submarine geological hazards in the Chengdao area are divided into four types: low risk, relatively low risk, relatively high risk, and high risk. The results show that the areas with a high geological hazard risk in this region are mainly distributed in the areas with water depths of 9-12 m, where the hydrodynamic effect is strong, with many human engineering activities, and seriously suffered from geologic hazards.The study results can provide scientific basis for engineering construction and hazard prevention in the Chengdao area.